Soccer, the Passion that Dies Slowly in Ecuador - Nieto-Aguilar, Wilson Germán (2019)
The research work aims to investigate sports habits and the acceptance of the product ‘Ecuadorian professional soccer championship’, among the inhabitants of the Metropolitan District of Quito and surrounding valleys. The theoretical support is based on secondary sources that allow understanding the soccer market in Ecuador. The reality of the market is evidenced by a quantitative study using the survey as a tool. From the research process results are obtained that are derived from 1 209 surveys: 11.56 % of people surveyed prefer to attend sports events in relation to football, while 66.50 % qualify between 1 and 7 the interest that awakens the championship of soccer in Ecuador, it is so that the ‘king of sports’ in Ecuador loses its throne as a mass spectacle.